PRAKTIK SENAM YOGA HUBUNGANNYA DENGAN KELANCARAN PROSES PERSALINAN - Annisa Ul Mutmainnah (Universitas Widya Gama Mahakam Samarinda, 2016)
Maternal Mortality Rate (MMR) in Indonesia is higher than other countries, even among Asian countries. Exercise during pregnancy is the one of method to prepare delivery process and further is to prevent maternal death. The objective of this research is to analyze relationship between knowledge and Gymnastics Yoga In Pregnancy, also relationship between Gymnastics Yoga In Pregnancy and delivery process. This was a cross sectional research. Moreover, the population involve in this research were all primi para (mother that having first pregnancy) that recorded at Air Putih Public Health Service Centre in Samarinda. The samples were taken by simple random sampling method. Furthermore, the relationship among variables was analyzed using chi square and fisher exact test. The result shows that there was no relationship between knowledge and Gymnastics Yoga In Pregnancy (p = 0.060), but there was a relationship between Gymnastics Yoga In Pregnancy and delivery process (p = 0.000). According to result of the research, it’s suggested that health promotion by doing Gymnastics Yoga In Pregnancy should be developed because it can prepare physically and psychologically of delivery process and reduce the risk of maternal death.